Paediatric surgery - Davenport, Mark; Coppi, Paolo De (Oxford : Oxford University Press, 2020)
Providing a concise but detailed contemporary overview of paediatric surgery, this second edition of the specialist handbook is a key revision tool for UK and European post-graduate exams, as well as giving the reader a clinical primer based around problem-solving and diagnosis.
This edition also issued in print: 2021.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on November 18, 2020).
Keywords: Children -- Surgery